Percy Jackson and the Sea of Monsters - "Riordan, Rick" (London; Puffin", 2013)
Demi-god Percy Jackson and his friends must journey into the Sea of Monsters to save their camp. But first Percy will discover a secret that makes him wonder whether being claimed as Poseidon's son is an honour or a cruel joke.
Keywords: English Fiction- Children's stories